Структура популяции дикого кабана (Sus scrofa) в степной Украине - Волох, А.М. (Вестник зоологии, 2002)
Приведены результаты изучения южноукраинской популяции кабана, образовавшейся в результате естественного расселения подвида Sus scrofa attila, а также интродукции подвидов S. s. ussuricus и S. s. scrofa. В популяции ежегодно размножается около 80% всех самок, плодовитость которых составляет 7,21 ± 0,26 поросят. В течение первого года жизни более 50% их погибает. Главными причинами смертности являются охота, гибель в оросительных каналах, голод в суровые зимы и нападение волков. В 1976—2001 гг. в степной популяции кабана 58,6% составляли поросята, 14,3% – подсвинки, 11,5% – взрослые самцы и 15,6% – cамки. Своеобразием группировки является образование больших стад от 15 до 42 особей в искусственных лесах и поймах крупных рек. Results of the investigation of South Ukraine population of the wild boar, formed as a result of natural distribution of the subspecies Sus scrofa attila, as well as introduction of S. s. ussuricus and S. s. scrofa are presented in the article. About 80% of the wild boar females reproduce annually. Their fertility is 7.21 ± 0.26 piglets. During the first year of their life more than 50% of them die. Main causes of the wild boars’ mortality are hunting, dying in irrigation canals, starvation in severe winters with long-term snowfalls, ice-cover on the ground and predacious of wolves. In 1976—2001 the wild boar steppe population included 58.6% of juveniles (1st year of life), 14.3% of yearling (2nd year of life), 11.5% of adult males and 15.6% of females. Peculiarity of the population is the formation of large groups, which consist of 15—42 animals in artificial forest plantations (which cover an area up to 2,000 ha) and in floodplains of large rivers.